Puhunang Pangkaunlaran ng Sikap Buhay (PPSB): A Micro-Financing Program of the Quezon City Government - Zabat, Maria Eloisa D. Almario (Review of Women's Studies; Vol 13 No 2 (2003): Review of Women's Studies Volume XIII, Number 2 (July-December 2003), 2004)
---